Adoption, non-adoption, and abandonment of a personal electronic health record: case study of HealthSpace. (16th November 2010) - Greenhalgh, Trisha; Hinder, Susan; Stramer, Katja; Bratan, Tanja; Russell, Jill
Abstract : Objective To evaluate the policy making process, implementation by NHS organisations, and patients' and carers' experiences of efforts to introduce an internet accessible personal electronic health record (HealthSpace) in a public sector healthcare system. Design Mixed method, multilevel case study. Setting English National Health Service; the basic HealthSpace technology (available throughout England) and the advanced version (available in a few localities where this option had been introduced) were considered. Main outcome measures National statistics on invitations sent, HealthSpace accounts created, and interviews and ethnographic observation of patients and carers. Data analysis was informed by a socio-technical approach which considered macro and micro influences on both adoption and non-adoption of innovations, and by the principles of critical discourse analysis. Participants 56 patients and carers (of whom 21 opened a basic HealthSpace account, 20 had diabetes but were not initially using HealthSpace, and 15 used advanced HealthSpace accounts to exchange messages with their general practitioner), 3000 pages of documents (policies, strategies, business plans, minutes of meetings, correspondence), observational field notes, and 160 interviews with policy makers, project managers, and clinical staff. Results Between 2007 and October 2010, 172 950 people opened a basic HealthSpace account. 2913 (0.13% of those invited) opened an advanced account, compared with 5-10% of the population anticipated in the original business case. Overall, patients perceived HealthSpace as neither useful nor easy to use and its functionality aligned poorly with their expectations and self management practices. Those who used email-style messaging were positive about its benefits, but enthusiasm beyond three early adopter clinicians was low, and fewer than 100 of 30 000 patients expressed interest. Policy makers' hopes that "deploying" HealthSpace would lead to empowered patients, personalised care, lower NHS costs, better data quality, and improved health literacy were not realised over the three year evaluation period. Conclusion Unless personal electronic health records align closely with people's attitudes, self management practices, identified information needs, and the wider care package (including organisational routines and incentive structures for clinicians), the risk that they will be abandoned or not adopted at all is substantial. Conceptualising such records dynamically (as components of a socio-technical network) rather than statically (as containers for data) and employing user centred design techniques might improve their chances of adoption and use. The findings raise questions about how eHealth programmes in England are developed and approved at policy level.